HUBUNGAN ANTARA RESILIENSI DAN SELF-EFFICACY DENGAN PRESTASI AKADEMIK MAHASISWA PREKLINIK DI FAKULTAS KEDOKTERAN UPNVJ TAHUN 2022 - Faizagina Istigfhar (2023)
Academic achievement is a student's achievement of assignments carried out in college that reflect the learning process and changes in insight, knowledge, behavior, and abilities. Several internal and external factors influence academic achievement. External factors include learning environment and infrastructure, as well as internal factors such as resilience, self-efficacy, and motivation. There need to be more studies regarding the relationship between resilience and self-efficacy with the academic achievement of preclinical students at the Faculty of Medicine. This research is also a new paradigm because of society's demands that health workers have resilience and confidence in carrying out their profession. Understanding resilience and self-efficacy is hoped to increase student academic achievement. This study aimed to determine the relationship between resilience and self-efficacy with the academic achievement of preclinical students at the UPNVJ Faculty of Medicine. The sampling method used stratified random sampling with 234 UPNVJ Faculty of Medicine students in 2019, 2020, and 2021 as the sample. The data was taken from a questionnaire filled out by the respondents. This study used a cross-sectional design. The correlation test in this study used the Spearman test. Statistical tests showed no significant relationship between resilience and academic achievement (p=0.747) and self-efficacy and academic achievement (p=0.106). Other factors may increase student academic achievement.